Remaking Miley: the effects of branding the celebrity brand, using Miley Cyrus as a case Study - Sayce, Chloe' Bijou (The IIE, 2016)
The present study focuses on examining the effects of rebranding the celebrity, using Miley Cyrus as a case study. The concept of celebrities as brands entails the theories of identity and personal branding. In the case of Miley Cyrus, the celebrity presents a situation where the brand image has noticeably changed. Prior to 2013, Cyrus exhibited an identity that was more in-line with that of the Disney brand image. However, at the 2013 VMAs (Video Music Awards), Cyrus presented a new brand identity that was a complete departure from her previous image and was widely considered to be controversial. The motivation for this paper is to explore the concept of celebrities as brands and how altering or evolving an existing celebrity brand image can affect the public consumption of that brand. The primary aim of this study is understand the consumer (Generation Y) reactions to the change in the celebrity brand, in order to examine the effects of rebranding the celebrity brand in terms of the consumer. In order to address this research problem two additional questions are addressed through the theory and analysis. The first question explores the issue of identity, how identity is constructed and the motivations behind celebrity attachment. The second question explores the concept of the celebrity and how the celebrity brand is constructed in relation to the consumer. In order to address the research problem this study adopts a mixed method research design, using an integration of both qualitative and quantitative research designs. Field research and non-experimental design are used as a means of data collection methods. Convenience and snowball sampling are used with the following population parameters: participants are between the ages 18-25 and have an existing knowledge of Miley Cyrus. This study makes use of the research instruments of standardised, open-ended interviews and a combination of open-ended surveys and self-completion questionnaires. The findings presented in the study suggest that our sense of self is constructed using brands as signifiers of who we are to others. It suggests that constructed identities are fluid and under constant revision. It also proposes that in terms of celebrity attachment, consumers align with brands that reflect a shared narrative. In the case of Miley Cyrus, the findings put forward that there is no complete rejection or acceptance of brand change, but rather consumers are selective in the acceptance, rejection, and adaption of elements of that change. The case study also suggests that changes in a brand run the risk of alienating consumers, however, they could begin to resonate with new consumers. The findings presented in the study suggest that the celebrity brand is constructed by the consumer based on their own identity. The implications of the findings are that, in terms of consumer reactions to change in celebrity brands, consumers are selective in their identification with celebrity brands and there is no complete acceptance or rejection as identity is a fluid construct. However, as is evident in the case study of Miley Cyrus, extreme brand changes destabilise the brand image and impact on the consumer connection to that identity construct as the very nature of the original relationship has been altered
Thesis
Keywords: Rebranding the celebrity; Miley Cyrus; Brand image; Public consumption; Consumer